2022
DOI: 10.34067/kid.0002152022
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced SHP-1 Expression in Podocyturia Is Associated with Kidney Dysfunction in Patients with Diabetes

Abstract: Background - Diabetic kidney disease (DKD) remains the leading cause of end-stage kidney disease worldwide. Despite significant advances in kidney care, there is a need to improve non-invasive techniques to better predict the progression of kidney disease for patients with diabetes. Following injury, podocytes are shed in urine and may be used as a biological tool. We previously reported that SHP-1 is upregulated in the kidney of diabetic mice leading to podocyte dysfunction and loss. Our objective was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Studies have shown that podocyteuria often precedes proteinuria in several renal diseases including DKD [ 19 ]. Therefore, detection of urine containing exfoliated podocytes plays a role in the early diagnosis of DKD [ 20 ]. Current research on podocyteuria includes the detection of functional proteins in podocytes in urine and the determination of microvesicles secreted by podocytes.…”
Section: The Roles Of Podocyte In Proteinuria and Podocyteuriamentioning
confidence: 99%
“…Studies have shown that podocyteuria often precedes proteinuria in several renal diseases including DKD [ 19 ]. Therefore, detection of urine containing exfoliated podocytes plays a role in the early diagnosis of DKD [ 20 ]. Current research on podocyteuria includes the detection of functional proteins in podocytes in urine and the determination of microvesicles secreted by podocytes.…”
Section: The Roles Of Podocyte In Proteinuria and Podocyteuriamentioning
confidence: 99%